The Grammatical Evidence between the Rigorous of the Rule and the Usage Optimality the Vocative Case Section - Oqlah, Moath Ahmed (Dirasat: Human and Social Sciences, 2025)
Objectives: are to uncover the methodology of grammarians in dealing with grammatical evidence in the context of vocatives and to demonstrate their commitment to maintaining grammatical rules by employing the linguistic preference theory to mitigate the rigidity of these rules. Method: The researcher used a descriptive-analytical method based on tracking the grammarians' approach to dealing with grammatical evidence in the context of vocatives. This involved analyzing these pieces of evidence in light of the linguistic preference theory, utilizing practical preference. Results: The research arrived at several conclusions, the most important being that the practical preference characteristic of the Arabic language allowed grammatical evidence to remain valid in grammatical studies. This is especially relevant as many violations in these pieces of evidence were marked by formal irregularities that did not impede communication between the speaker and the listener. Conclusion: The research concluded that the judgments made by grammarians on grammatical evidence were also influenced by the educational methodology. Additionally, Arabic grammar placed significant importance on the context accompanying the speech event in determining the speaker's intent. Furthermore, the vocative is an expressive category that can be interpreted contextually.